2018
DOI: 10.1093/eurheartj/ehy475
|View full text |Cite
|
Sign up to set email alerts
|

Asleep blood pressure: significant prognostic marker of vascular risk and therapeutic target for prevention

Abstract: Asleep SBP is the most significant BP-derived risk factor for CVD events. Furthermore, treatment-induced decrease of asleep, but not awake SBP, a novel hypertension therapeutic target requiring periodic patient evaluation by ambulatory monitoring, is associated with significantly lower risk for CVD morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
86
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 28 publications
5
86
0
3
Order By: Relevance
“…[47][48][49][50] The MAPEC clinical trial (2156 hypertensive participants with follow-up 5.6 years) similarly showed that evening (vs morning) administration of BP medications resulted in improved clinical outcomes with reduction in total cardiovascular events and death by 67%, and prevention of CKD. 9,22,[51][52][53][54] In contrast, there have been a few smaller-powered studies with various study designs that reported no difference between evening and morning administration of anti-hypertensive medications. 14,55 One such study, the HARMONY trial, transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50] The MAPEC clinical trial (2156 hypertensive participants with follow-up 5.6 years) similarly showed that evening (vs morning) administration of BP medications resulted in improved clinical outcomes with reduction in total cardiovascular events and death by 67%, and prevention of CKD. 9,22,[51][52][53][54] In contrast, there have been a few smaller-powered studies with various study designs that reported no difference between evening and morning administration of anti-hypertensive medications. 14,55 One such study, the HARMONY trial, transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These entities are independently associated with progressive kidney dysfunction, proteinuria, cardiovascular morbidity and mortality in adults with hypertension and CKD. [8][9][10][11][12][13][14] Whether pediatric transplant recipients with nHTN or non-dipping are at higher risk for cardiovascular outcomes in adult life is unknown due to the lack of long-term longitudinal studies; however, it has been shown that young adults with a history of kidney transplantation during childhood and adolescence have a greater than 10-fold risk of cardiovascular death compared with the general population. 15 Hence, restoring the nocturnal dip and normalizing nocturnal BP might be therapeutic targets with potential cardiovascular and kidney disease benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this evidence, many guidelines and reviews focus on morning BP as the object of BP management . However, there has been increasing interest in nocturnal BP as the BP parameter most closely related to cardiovascular risk . As recommended by Kario, controlling morning BP is only the first step toward perfect 24‐hour BP control and should be followed by the control of nocturnal hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Hermida et al, the asleep systolic BP was the most important risk factor for the primary outcome (defined as composite of cardiovascular death, myocardial infarction, coronary revascularization, heart failure and stroke) during 5.1-year median follow-up, and it was regardless of office and awake systolic BP values. The authors emphasize also the fact that attenuation of above-mentioned parameter was the most significant marker of eventfree survival [5].…”
Section: Introductionmentioning
confidence: 91%